THE SYSTEM-FORMING ROLE OF RATIONAL ORGANIZATION OF MANAGERIAL ACCOUNTING IN ENSURING SUSTAINABLE DEVELOPMENT OF CONSTRUCTION ENTERPRISES - Pylypiv , N.I.; Rudyi , M.V. (The actual problems of regional economy development, 2025)
The article explores the system-forming role of the rational organization of managerial accounting in ensuring the sustainable economic development of construction enterprises. It emphasizes the importance of establishing a high-quality information base that enables the adoption of well-grounded managerial decisions in a dynamic external environment. The purpose of the study is to investigate the role of rational managerial accounting organization as a key tool in forming an effective enterprise management system aimed at achieving sustainable development in the construction sector. The methodological basis of the research includes a systems approach, methods of structural-logical, comparative, and statistical analysis, as well as cognitive modeling. Based on official statistics on the volume of construction works carried out from 2018 to 2023, the article analyzes development trends in the industry, identifies periods of decline and growth, and examines the influence of external factors on the dynamics of these changes. The application of a cognitive map is proposed as a tool for visualizing the interconnections between managerial actions, accounting information, and enterprise performance. The article proves that a well-organized managerial accounting system ensures transparency in financial and production processes, contributes to risk mitigation, cost optimization, and efficient resource utilization. The scientific novelty lies in the conceptualization of managerial accounting as a system-forming factor in achieving the stable development of construction enterprises under modern economic conditions. The practical significance of the findings lies in the possibility of applying the proposed approach in real-world management practices of construction companies to enhance their adaptability and competitiveness. The conclusions confirm that rational organization of managerial accounting, combined with cognitive modeling tools, makes it possible to develop flexible management systems capable of promptly responding to changes, implementing innovations, and ensuring the long-term growth of the construction business.